Upaya Meningkatkan Kemampuan Mengenal Huruf Menggunakan Media Kartu Kata Murid Kelompok B RA Samanhudi Kecamatan Tanete Riattang Kabupaten Bone - Nurhayati Nurhayati (Universtas Negeri Makassar, 2021)
This study aims to improve the process of learning activities and the ability to recognize the letters of group B children RA Saman Hudi through the learning process by applying word card media. The type of research conducted is classroom action research (Classroom Action Research) which will be carried out in 2 cycles. The subjects of this study were the children of group B RA Saman Hudi, Tanete Riattang District, Bone Regency in 2020 with a total of 15 children. Data collection techniques using observation and documentation techniques. The validation techniques used in this study are member check, triangulation, and audit trail. Observational data were analyzed descriptively quantitatively. The results showed that the use of word card media can improve the ability to recognize letters of RA Saman Hudi's students, Tanete Riattang District, Bone Regency. Based on the results of the study, it can be concluded that through the use of word card media it is proven to be able to improve the ability to recognize letters in group B children RA Saman Hudi, Tanete Riattang District, Bone Regency.